Closing the attainment gap in schools : progress through evidence-based practices - Luby, Antony (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Closing the Attainment Gap in Schools explores the experience and history of teachers who have a determined, no-nonsense approach to providing an excellent standard of education to all young people from differing backgrounds. Using professional conversations, voices are given to schools and teachers striving successfully to address this important issue through evidence-based practices. Linked with the Ad Astra Primary Partnership, what these teachers do with their schoolchildren will resonate with all schools in any location. From Superstar Assemblies to encourage their dreams and aspirations; to Munch n Mingle sessions to encourage healthy eating; to Marvellous Me software to encourage the use of open-ended questions and parent-child conversations at home; and through to the use of skilled specialists to develop their handwriting skills, this book: explores the rich complexity of teacher learning; contains numerous case studies and examples of success; reflects upon and considers evidence-based pedagogy, practical wisdom, teacher-research, self-improving school systems and social justice; proposes a rich array of approaches and suggests ways forward. Offering first-hand, invaluable and practical advice this wide-ranging book will encourage and enable any teacher to develop their own practical wisdom and a can do' approach whilst never shying away from the very real issues within education.
OCLC-licensed vendor bibliographic record.
Keywords: Academic achievement -- Great Britain; Educational attainment -- Great Britain; EDUCATION / General